The Times Higher Education Rankings and the Mysterious “Rise of Asia” - Usher, Alex (International Higher Education, 2015)
The Times Higher Education Rankings analysis of its own rankings have persistently pushed a “rise of Asia” narrative – by which the paper usually means East Asia. But this year, the narrative was only sustained by the surprise rise of Turkey in the rankings – a rise that was to significant extent precipitated by a single highly-cited scientific paper.